Criminal Liability in Cases of Counterfeiting Excise Stamps under Indonesian Excise Law - Sastradinata, Dhevi Nayasari; Ja'far Shodiq; Maulana, Syahrul Hikmah (Jurnal Independent, 2025)
Criminal acts in the field of excise in this case are closely related to counterfeiting excise stamps which will have an impact on two sides, namely affecting state revenue and damaging the social system. In addition, the Criminal Act of counterfeiting excise stamps is a special criminal act regulated in Law Number 39 of 2007 concerning Amendments to Law Number 11 of 1995 concerning Excise. The formulation of the problem in writing this law is how to investigate counterfeiting excise stamps and apply criminal sanctions to counterfeiting excise stamps according to Law Number 39 of 2007 concerning Excise. This study uses a normative juridical research type using a statute approach and a conceptual approach. The legal materials in this study are primary legal materials and secondary legal materials. The results of this study conclude that in the process of investigation of PPNS Customs and Excise regulated in the applicable legislation in Law Number 39 of 2007 concerning Amendments to Law Number 11 of 1995 concerning Excise, and Laws Number 17 of 2006 concerning Amendments to Laws Number 10 of 1995 concerning Customs and Excise, it is regulated regarding the authority of civil servant investigators of the Directorate General of Customs and Excise and is based on Government Regulation Number 55 of 1996 until August 23, 1996. The criminal law policy in efforts to overcome the crime of counterfeiting excise tapes currently contained in the Criminal Code still has weaknesses in the rules regarding investigations into counterfeiting excise tapes and the application of sanctions. Therefore, the criminal law policy in the effort to overcome the crime of counterfeiting excise stamps in the future must be regulated better in the application of sanctions, so that it can help law enforcers in upholding justice and judges in deciding a case.